2018
DOI: 10.1111/ejn.14154
|View full text |Cite
|
Sign up to set email alerts
|

Verbal working memory modulates afferent circuits in motor cortex

Abstract: Verbal instruction and strategies informed by declarative memory are key to performance and acquisition of skilled actions. We previously demonstrated that anatomically distinct sensory-motor inputs converging on the corticospinal neurons of motor cortex are differentially sensitive to visual attention load. However, how loading of working memory shapes afferent input to motor cortex is unknown. This study used short-latency afferent inhibition (SAI) to probe the effect of verbal working memory upon anatomical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 34 publications
5
21
1
Order By: Relevance
“…Cognitive processes, for instance attention and working memory, shape afferent sensory-motor integration involving distinct intracortical circuits as demonstrated by single monophasic TMS pulses that evoke different current directions in the brain (Mirdamadi et al, 2017; Suzuki and Meehan, 2018). Specifically, it has been demonstrated that SAI evoked using antero-posterior (AP), but not posterior-anterior (PA), current is reduced by a concurrent visual detection task with high attention demands.…”
Section: Short-latency Afferent Inhibition In the Healthy Human Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive processes, for instance attention and working memory, shape afferent sensory-motor integration involving distinct intracortical circuits as demonstrated by single monophasic TMS pulses that evoke different current directions in the brain (Mirdamadi et al, 2017; Suzuki and Meehan, 2018). Specifically, it has been demonstrated that SAI evoked using antero-posterior (AP), but not posterior-anterior (PA), current is reduced by a concurrent visual detection task with high attention demands.…”
Section: Short-latency Afferent Inhibition In the Healthy Human Brainmentioning
confidence: 99%
“…These results suggested that only AP-elicited intracortical circuits are sensitive to cross-modal attention task by altering sensory processing in premotor areas (Mirdamadi et al, 2017). Instead, a verbal working memory task modulated SAI, regardless of the TMS-induced current direction in the brain (AP or PA), reflecting a generalized effect of this cognitive task across anatomically distinct circuits upon cortico-spinal neurons in the M1-HAND (Suzuki and Meehan, 2018).…”
Section: Short-latency Afferent Inhibition In the Healthy Human Brainmentioning
confidence: 99%
“…As an example of sensorimotor modulation derived from higher order cognitive processes, a decreased sensorimotor inhibition has been observed during a verbal working memory task, with increasing memory set size 42 . Indeed, SAI was significantly reduced during memory maintenance of six-digit compared to two-digit set 42 .…”
Section: Discussionmentioning
confidence: 99%
“…As an example of sensorimotor modulation derived from higher order cognitive processes, a decreased sensorimotor inhibition has been observed during a verbal working memory task, with increasing memory set size 42 . Indeed, SAI was significantly reduced during memory maintenance of six-digit compared to two-digit set 42 . This result was interpreted as the necessity to increase the suppression of the task-irrelevant somatosensory afferent projections to motor cortex during the maintenance period of the verbal working memory task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation